Comparative Study on the Application of the Ultimum Remedium Principle in Excise Law: A Comparative Analysis Between Indonesia and ASEAN Countries - Handoko Nindyo Wardono; Boy Nurdin (Ridwan Institute, 2026)
This research evaluates the effectiveness of criminal law enforcement against illegal cigarette excise violations in Indonesia using a socio-legal approach and regional comparisons within the ASEAN region. Empirical data from 2021 to 2024 show that, despite a significant increase in enforcement operations from 5,100 to 8,900 cases, the percentage of illegal cigarettes remained stagnant at around 4 to 6 percent. These findings indicate the ineffectiveness of a purely penal approach in changing market dynamics, mainly due to the existence of legal pluralism, which triggers avoidance responses and conflicts between MSME actors and state law. A comparative study of four ASEAN countries, namely the Philippines, Thailand, Malaysia, and Vietnam, confirms that administrative instruments, distribution supervision, and the use of technology play a much more significant role in supporting the effectiveness of law enforcement than criminal instruments. Based on these findings, the study recommends reconstructing the excise law enforcement mechanism by prioritizing the ultimum remedium principle, whereby the application of criminal penalties is used only as a last resort and is focused on syndicates or large-scale perpetrators. Meanwhile, violations committed by MSMEs should be resolved through a Restorative Fiscal Justice approach in accordance with PP 54/2023, which is oriented toward fiscal recovery and supported by the qualitative differentiation of violators and the simplification of licensing procedures.